Long‐Term Impact of Early Life Events on Physiology and Behaviour. (September 2014) - Boersma, G. J.; Bale, T. L.; Casanello, P.; Lara, H. E.; Lucion, A. B.; Suchecki, D.; Tamashiro, K. L.
<x xml:space="preserve">Abstract</x> This review discusses the effects of stress and nutrition throughout development and summarises studies investigating how exposure to stress or alterations in nutrition during the pre‐conception, prenatal and early postnatal periods can affect the long‐term health of an individual. In general, the data presented here suggest that that anything signalling potential adverse conditions later in life, such as high levels of stress or low levels of food availability, will lead to alterations in the offspring, possibly of an epigenetic nature, preparing the offspring for these conditions later in life. However, when similar environmental conditions are not met in adulthood, these alterations may have maladaptive consequences, resulting in obesity and heightened stress sensitivity. The data also suggest that the mechanism underlying these adult phenotypes might be dependent on the type and the timing of exposure.